Prognostic value of circulating tumour DNA in patients undergoing curative resection for pancreatic cancer - Hadano, Naoto (Br J Cancer, 2016)
BACKGROUND: Pancreatic ductal adenocarcinoma (PDAC) is frequently diagnosed at an advanced stage, leading to a poor prognosis. Therefore, interest in the development of non-invasive biomarkers for prognostic prediction has grown rapidly. Here, we assessed the clinical implications of v-Ki-ras2 kirsten rat sarcoma viral oncogene homolog (KRAS)-mutated circulating tumour DNA (ctDNA) as a useful surrogate biomarker in patients with resectable PDAC. METHODS: We used droplet digital polymerase chain reaction to detect rare mutant tumour-derived KRAS genes in plasma cell-free DNA (cfDNA) as ctDNA. Samples were collected from 105 patients who underwent pancreatoduodenectomy for PDAC at a single institution. Overall survival (OS) was analysed according to the presence of ctDNA. RESULTS: Among the 105 cases, ctDNA was detected in 33 (31%) plasma samples. The median OS durations were 13.6 months for patients with ctDNA (ctDNA+) and 27.6 months for patients without ctDNA. Patients who were ctDNA+ had a significantly poorer prognosis with respect to OS (P<0.0001). CONCLUSIONS: Our findings suggested that the presence of ctDNA in plasma samples could be an important and powerful predictor of poor survival in patients with PDAC. Accordingly, ctDNA detection might be a promising approach with respect to PDAC treatment.